Implementasi Metode Tikrar dalam Meningkatkan Kualitas Hafalan Al Qur’an pada Santri Kelas VII Bintang Rabbani Boarding School - Izuddin Lubis, Muhammad; Safrijal, Safrijal; Yurmaini, Yurmaini (Jurnal Ilmu Pendidikan Islam, 2024)
This study aims to describe the implementation of the Tikrar method in improving the quality of Al-Qur'an memorization in class VII students at Bintang Rabbani Boarding School. The Tikrar method is a continuous memorization repetition technique that aims to strengthen students' memory of the verses that have been memorized. This study uses a qualitative approach with a case study method. Data collection techniques are carried out through observation, in-depth interviews with tahfidz teachers and students, and documentation of students' daily activities in the memorization process. The results of the study showed that the Tikrar method was routinely applied in tahfidz activities, both through independent repetition and teacher guidance. Repetition was carried out in a structured manner with certain targets every day. Although there were several obstacles such as lack of time discipline, differences in students' memorization abilities, and fatigue due to dense activities, the Tikrar method was still proven effective in improving the quality of memorization. Students who were consistent in applying this method showed significant improvements in terms of fluency, accuracy, and memorization endurance. Therefore, the implementation of the Tikrar method at Bintang Rabbani Boarding School has a positive impact on the quality of students' memorization of the Qur'an. The success of this method is greatly influenced by the discipline of students, teacher support, and good time management. Therefore, the Tikrar method is worthy of being continuously developed and optimized in the tahfidz learning program in the Islamic education environment.